2018
DOI: 10.1017/mor.2017.57
|View full text |Cite
|
Sign up to set email alerts
|

The CEO Horizon Problem and Managerial Slack in China

Abstract: This study investigates how CEO behavior and incentives change during the CEO's final years in office, known as the horizon problem. We examine how the horizon problem alters managerial slack, a measure of operational inefficiency and managerial value diversion. Using data on Chinese publicly traded firms between 2003 and 2011, we find that managerial slack increases in the last two years of CEO tenure compared to earlier years. We also show that the increase in managerial slack in CEO final years in office is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 105 publications
2
7
0
Order By: Relevance
“…This finding is in supports of Baik et al (2011) and Zouari et al (2015), who show that longer serving managers use the opportunity to engage in managing the reporting earnings. The results are also consistent with outcome of Fang et al (2018) who find that managerial slack turned to increase in CEO's final years in office.…”
Section: Regression Resultssupporting
confidence: 87%
“…This finding is in supports of Baik et al (2011) and Zouari et al (2015), who show that longer serving managers use the opportunity to engage in managing the reporting earnings. The results are also consistent with outcome of Fang et al (2018) who find that managerial slack turned to increase in CEO's final years in office.…”
Section: Regression Resultssupporting
confidence: 87%
“…Hence, this study examines whether firms with listed or non-listed GDRs/ADRs attract more foreign investors in Pakistan. Klapper et al (2006) suggest that if the country-level governance conditions are substandard, then firm-level corporate governance matters more for the investors since effective corporate governance mechanism in a firm reduces the likelihoods of expropriation by firm managers (Shleifer and Vishny, 1997;Fang et al, 2018;Sch€ auble, 2019). In a similar vein, Ferreira and Matos (2008) find that foreign institutional investors have a strong tendency for the stock of firms with good corporate governance.…”
Section: Determinants Of Foreign Investment In Pakistanmentioning
confidence: 92%
“…The manager-owner agency problem is serious in Chinese SOEs ( Fan et al, 2007 ; Fang et al, 2018 ). Under this institutional context and combined with the above analysis, we propose the first hypothesis:…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Our findings also imply that in SOEs, CFOs’ functionally diverse experience leads to their lack of identity as heads of accounting departments and makes the CFOs more like political officials rather than professional managers ( Hu and Xu, 2021 ). Many scholars have found that, in China, CEOs with different labels have different impacts on firms’ financial policies ( Fan et al, 2007 ; Li and Qian, 2013 ), especially for those at SOEs ( Xie, 2015 ; Fang et al, 2018 ; Lou et al, 2021 ). This paper thus expands the research scope and provides an understanding of other executives in Chinese SOEs.…”
Section: Summary and Commentsmentioning
confidence: 99%